The lmpact of zahoreck Model in learning some Basic Skills in Football - Dr. Muhanad Mohammad Kareem (Global Scientific Publishing, 2024)
The multiplicity of advanced methods, methods, and strategies in teaching and delivering clear, quick, and correct information to learners and their ability to perform the skills. Accordingly, the imperative method and the Zahorik model aim to achieve the goal of learning, and from here comes the importance of research in developing and improving the level of learners in the game of football and communicating the required goals to learners. One of the most important goals of the research is to know the effect of the imperative method and the Zahorik model in learning some basic football skills
Keywords: imperative; model; communicating; skills